English Communicative Competence of Health Vocational High Schools (Case Study at Health Vocational High Schools in Internusa Institution in Central Java) - Setyowati, Ratini; Setiawati, Beta; Wardhani, Evi Murti (Journal of English Teaching and Learning Issues, 2020)
Indonesia must prepare the high-skill categories needs for every aspects. One of the aspects is the ability to compete in this era, the ability to communicate with other. Indonesian needs English communicative skill to face the Industrial Revolution 4.0. The aims of the study are: understand Vocational High Schools students’ English communicative competence and to understand the teaching method on Improving English Communicative competence for Health Vocational High Schools. This research used descriptive qualitative method. The study used a TOEIC Test to know the result of the study and interview the English teachers, the populations of the study are the third grades of Health Vocational High Schools at Internusa Institution in Central Java, there are 552 students from 6 Health Vocational High Schools. The results of the study is the students English Communicative competence is still on score 186-250 (Memorized Proficiency). The teachers have appled many methods to improved the English Communicative competence. most of the applied Discovery Learning Method.